Integrating Climate Literacy into Teacher Education Programs: A Framework for Future Teachers - Bhoi, Chandrasekhar; Dash, Sagnika; Adi, Prakash Chandra (Journal of Education Method and Learning Strategy, 2025)
Climate change poses significant challenges to global sustainability, making climate literacy an essential component of contemporary education. Yet, teacher education programs often lack structured approaches to prepare pre-service teachers for integrating climate-related content into their future classrooms. This paper presents a comprehensive framework for embedding climate literacy into teacher education, aiming to equip future educators with the knowledge, skills, and values needed for effective climate and sustainability instruction. The study outlines the current deficiencies in teacher preparation, defines the scope of climate literacy within the educational context, and offers interdisciplinary, actionable strategies for curriculum developers and teacher educators. By aligning teacher education with international sustainability goals, this framework supports the cultivation of environmentally responsible citizens and climate-resilient education systems.